New Ways through the Alps The New Gotthard Base Tunnel - Impact of a Big Construction Site on a Small Mountain Village - Simone Strauf; Manfred Walser (European Regional Science Association (ERSA), 2005)
For Switzerland as located in the heart of Europe transport policy is a matter of particular importance. Especially transports between Italy and Germany use the Swiss corridors through the Alps. Therefore Switzerland realised a most ambitious construction project called NEAT (Neue Alpen Transversale) to improve the European train connections especially for freight transports. One part of the project is the new Gotthard base tunnel, the longest railway tunnel of the world and the most impressive element of the new transalpine railway line through the Alps. In view of the difficult accessibility and extreme climatic conditions, ensuring the fast and reliable transit of more than 300 trains per day through the two 57 km long single-track galleries represents a considerable technical challenge. The Gotthard base line directly links the northern and southern sides of the Alps and the project of building a new line should achieve the following goals: Massive increase in goods capacity (twice as much as today) Much shorter North-South transit time for passengers and freight Reduced traction power requirements, per weight unit of transported goods, as a result of the elimination of steep slopes. The construction work started in 1996 and will be probably finished by 2013. Because of the length of the tunnel five points were chosen, from which the drilling started. The shortest but technical most challenging phase of construction is located under the small village of "Sedrun” in the canton of "Graubünden”. Sedrun is a tourism destination for skiing, 1335 m above sea level with about 1.500 inhabitants. Here a gallery leads to a mine shaft with a depth of 800 m, ending at 550 m above sea level. At the intermediate access of Sedrun a multifunctional station is located which also is used for crossover, air ventilation, technical infrastructure and in case of emergency. The construction site with its enormous needs on resources, infrastructure, workforces - for example at the beginning a lot of specialists from South African mining branch came to Sedrun – may be a big challenge for the small village. In 2004 during the peak period up to 400 workers have been employed. Also logistical solutions for the transport of machines and material to the construction side and the carrying of stone to the deposits have to be developed. An ongoing long-term accompanying research (2000 – 2013) is analysing the ecological, economic and social impact on the construction site for the village and the region. The research project wants to assess the sustainability of such a long-term construction process. The contracting body is an advisory group of public institutions including the community of Sedrun, the region 'Obere Surselva', the canton Graubünden and the Swiss Federal Office of Transport. Within the long-term research a set of indicators will be collected every year furthermore an every third year deep-rooted analysis on different topics will be done. The project also has the function of an early-warning system to anticipate unexpected stresses and strains. The results of the research will be visualised from a documentary film team. Besides the annual research we tried to answer the following question: Which are the economic impacts of the construction site for the region of Sedrun? The decision to choose Sedrun as one of the five construction sites for the Gotthard base tunnel did not only change the ecological and social situation in the region but also has economic effects on the community. Especially the local building sector but also hotels, restaurants and local industry are benefiting from the construction site. To calculate these economic effects for the region of Sedrun we used the method of the incidence analysis. The incidence analysis is a kind of cost-benefit analysis which is especially suited to assess the spatial effects of infrastructural facilities or the service of these facilities. Considering the direct effects we focus on the receipts and expenditures which are directly connected with the realisation of the project. The economic effects could be divided into the so called tangible and intangible effects. Tangible effects are measurable as indirect economic effects (spill-over effects). To measure the indirect economic effects we carry out an interview survey among the workers to calculate the additional economic impacts caused by the expenditures of the workers in the region. The intangible effects could be explained as soft and mostly not quantifiable effects. To acquire the intangible effects we carry out an image analysis based on national newspaper articles about the construction site in Sedrun. In our paper we present the structure and main indicators of the long-term accompanying research and the results of the incidence analysis to calculate the economic effects for the region.
Keywords: 330